1989
DOI: 10.3109/00365528909089228
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio of Pepsinogen A to Pepsinogen C: A Sensitive Test for Atrophic Gastritis

Abstract: To diagnose fundic atrophic (type A) gastritis as part of the clinical investigation of various diseases or for epidemiologic purposes, a simple and reliable diagnostic test would be of great value. We studied circulating levels of pepsinogen A (PGA) and pepsinogen C (PGC) in 179 patients with fundic atrophic gastritis, 29 unselected patients with gastric adenocarcinoma, 15 totally gastrectomized patients, and 50 gastroscopically examined normal controls. Of 147 patients with severe atrophic gastritis, 42 (29%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 23 publications
5
63
0
Order By: Relevance
“…[41][42][43] We utilized the validated cutoff levels employed routinely in Japan, namely, a PG I level of < 70 ng/ml and a PG I:II ratio of < 3.0. [44][45][46] Thus, we feel confident that the designation of atrophy was accurate and reflected the important histologic entity of corpus atrophy. In summary, we have found that a polymorphism in the PTPN11 gene that encodes SHP-2 increases the risk of gastric atrophy in H. pylori-positive patients.…”
Section: Discussionmentioning
confidence: 88%
“…[41][42][43] We utilized the validated cutoff levels employed routinely in Japan, namely, a PG I level of < 70 ng/ml and a PG I:II ratio of < 3.0. [44][45][46] Thus, we feel confident that the designation of atrophy was accurate and reflected the important histologic entity of corpus atrophy. In summary, we have found that a polymorphism in the PTPN11 gene that encodes SHP-2 increases the risk of gastric atrophy in H. pylori-positive patients.…”
Section: Discussionmentioning
confidence: 88%
“…In the previous studies, no cut-off values were demonstrated to be related to serum PG I level and PG I / PG II ratios. In similar studies on this subject, different cut-off values were used, and the sensitivity and specificity were reported to range from 74.3-93% and 68.4-100%, respectively [8,[19][20][21][22]. The current study shows that cut-off values for the serum PG I level <25 ng/ml and the serum PG I / PG II ratio <3.0 would be convenient and meaningful for stomach cancer and atrophic gastritis screening.…”
Section: Discussionmentioning
confidence: 99%
“…At these cut-off values, Kitahara et al (37) reported a sensitivity of 84.6% and specificity of 73.5% in gastric cancer screening. In a study by Borch et al (40), serum PGI level of ≤71.6 µg/l had a sensitivity of 100% and specificity of 86%, while the serum PGI:II ratio of ≤5.5 had a sensitivity of 99% and specificity of 94% in diagnosing fundal CAG. A previous study reported that an accuracy of 83%, sensitivity of 83% and specificity of 95% using different serum PGI and G-17 cut-off values to diagnose CAG depending on the HpAb level (21).…”
Section: Histological Finding ---------------------------------------mentioning
confidence: 99%